ANALISA PUTUSAN PERKARA PERDAGANGAN ORANG BERDASARKAN AJARAN CONCURSUS REALIS (STUDI KASUS PUTUSAN NOMOR 69/PID.SUS/2021/PN.SKM) - Redha, Raju Kana; Trisna, Nila (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2022)
Trafficking in persons and exploitation of children is a very serious problem and needs to be discussed further legally because it involves human rights issues related to all forms of violence, torture, neglect of the dignity of women and children in society. This article wants to analyze the basis and how the judge's considerations in qualifying the sentence in giving the decision are in accordance with the provisions of the Concursus Doctrine. This study is for the sake of achieving the actual objective of sentencing. The goal to be achieved in this research is how the provisions of the Concursus teachings regarding judges are considered in qualifying sentences with Article 17 Law No 21 of 2007 concerning TIP. In this article the research method used is empirical legal research using descriptive methods, where this research requires research in the form of direct field interviews and uses library research which requires references from applicable laws and regulations. With regard to the idealistic and realist Concursus provisions of the judge, in this writing he is of the opinion that if the decision in qualifying the defense is a mistake because the general Concursus court provisions for the perpetrator's actions state that if an act is included in more than one criminal provision, then only one of those provisions shall be is used, then what is used is the provision with the heaviest principal sentence, but in sentencing in this case the basis used by the judge is Article 65 of the Criminal Code, which base has provisions, namely Concursus realis, which in the maximum sentence may not be more than 20 years and the maximum sentence the heaviest plus one-third.